Clinical manifestations and imaging and pathological features of giant cell angioblastoma: Report of four cases and literature review - Li, Qingbin; Zhang, Zhaohua; Chen, Guocai; Hu, Yongbo; Mao, Rongjun; Xie, Le; Chen, Shaoluan; Lao, Yongqiang; Gao, Junqing (Frontiers in Surgery, 2023)
Giant cell hemangioblastoma is a relatively rare vasogenic tumor.So far, studies on its clinical manifestations,imaging characteristics or pathological features as well as prognosis are extremely limited and unknown with only a few cases recorded.In this study,4 cases of giant cell hemangioblastoma confirmed by pathological examination were reported to improve our understanding and deep exploration of the tumor spectrum. All cases in our study are male, including 2 adults and 2 boys. The lesions were located in the lower segment of the femur, medial condyle of femur, knee joint and popliteal fossa respectively. Regarding the imaging characteristics, 2 patients with lesions in bone showed bone destruction, while the other 2 invading soft tissues, showing irregular abnormal signal shadow and obvious enhancement. Histopathological analysis revealed that the nodular tumor tissue was mainly composed of oval and spindle cells, with varying number of osteoclast-like multinucleated giant cells, and the interstitial tissues was often fill with blood vessels of different sizes. The immunophenotype demonstrates that endothelial cells of small vessels in nodules expressed CD31, SMA and ERG, while the osteoclast-like multinucleated giant cells and histiocytes express CD68 and CD163, and the surrounding cells express SMA. All 4 patients were treated with surgical resection. One of them relapsed 1 month after surgery and received a second surgical resection. No distant metastasis or death occurred during the follow-up period. This study indicates that giant cell hemangioblastoma is a local invasive vascular tumor which can develop both in infants and adults with skin, mucous membrane, soft tissue and bone involvement. Imaging characteristics shows bone destroyed and irregular abnormal signal shadow, in the meanwhile, obvious morphological characteristics can be observed. Currently, the treatment is mainly surgical resection, and interferon may be used as an adjuvant chemotherapy.